Lidocaine versus plain saline for pain relief in fractional curettage: A randomized controlled trial - Boonsri Chanrachakul (2018)
OBJECTIVE: To compare the efficiency of lidocaine with that of plain saline for paracervical pain relief during fractional curettage. METHODS: This double-blind, randomized, controlled trial included 140 women who underwent fractional curettage. Seventy women were allocated to the lidocaine group and 70 to the plain saline group. The main outcome measure was the intensity of pain measured by visual analog scale during and after the procedure. RESULTS: The intensity of pain was significantly lower in the lidocaine group than in the plain saline group over the course of the procedure (P=.02), especially during fractional curettage. There were no serious adverse effects in this study. CONCLUSION: Lidocaine is more effective than plain saline for paracervical pain relief during fractional curettage. The anesthetic mechanisms of lidocaine are mechanical distention of tissue and peripheral nerve block. © 2001 by the American College of Obstetricians and Gynecologists.